A kind of autotrophic denitrification filler for denitrification and preparation method thereof

By pretreating sulfur powder and adding a variety of raw materials, the pore structure and adhesion of the autotrophic denitrification filler for nitrogen removal is optimized, and the problem of limited contact reaction area of ​​existing fillers is solved, which significantly improves the purification effect.

CN119524790BActive Publication Date: 2025-03-25SHANDONG LONGANTAI ENVIRONMENTAL PROTECTION SCI TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510080426.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-03-25
Estimated Expiration
2045-01-20

AI Technical Summary

Technical Problem

The surface pore structure of the existing autotrophic denitrification fillers for nitrogen removal is relatively single, resulting in limited contact reaction area between the filler and sewage, affecting the purification effect.

Method used

By pretreating sulfur powder, including water bath heating and soaking, ultrasonic dispersion and drying, a mixture of sulfur powder with different particle sizes is generated, and raw materials such as zinc carbonate powder, iron tetraoxide, polyhydroxy fatty acid esters, sugarcane cellulose, cotton, etc. are added to optimize the pore structure and adhesion of the filler.

Benefits of technology

It effectively improves the specific surface area and pore structure complexity of the filler, increases the contact area between the filler and sewage, promotes the adhesion and growth of denitrifying bacteria, and significantly improves the purification effect of autotrophic denitrifying filler for denitrification.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119524790B_ABST
    Figure CN119524790B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of denitrification fillers, specifically to an autotrophic denitrification filler for denitrification and a preparation method thereof: comprising the following raw materials by weight: 80 to 100 parts of sulfur powder, 8 to 12 parts of zinc carbonate powder, 8 to 12 parts of clay, 4 to 6 parts of ferroferric oxide, 4 to 6 parts of polyhydroxyalkanoate, 4 to 6 parts of sugarcane cellulose, 1 to 3 parts of cotton, 1 to 3 parts of binder and 1 to 3 parts of cross-linking agent. In the present invention, in high-frequency ultrasonic treatment, the contact between sulfur powder and sodium sulfide is uneven, and then uneven concave dissolution positions can be generated on the surface of sulfur powder, so that the specific surface area of ​​sulfur powder is effectively increased. After sulfur powder is used as the main raw material to make filler, the filler has a large contact reaction area with sewage, providing a good attachment and growth environment for denitrifying bacteria, and improving the purification effect of autotrophic denitrification filler for denitrification.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of denitrification fillers, in particular to an autotrophic denitrification filler for denitrification and a preparation method thereof. Background Art

[0002] Autotrophic denitrification filler for denitrification is a purification material made of sulfur as the main component. The denitrification filler is oxidized during the denitrification process, providing energy for autotrophic denitrifying bacteria to convert nitrate nitrogen into nitrogen gas. It can be used for deep denitrification treatment in municipal sewage treatment plants.

[0003] In the prior art, the autotrophic denitrification filler for denitrification is made of sulfur powder as the main raw material during the preparation process. However, after a large amount of powdered raw materials are formed into fillers, the raw materials are evenly distributed after mixing, which will cause the surface pore structure of the filler to be relatively simple, so that the contact reaction area between the filler and the sewage is limited, thereby affecting the purification effect of the filler. Based on this, the present invention provides an autotrophic denitrification filler for denitrification and a preparation method thereof. Summary of the invention

[0004] The purpose of the present invention is to provide an autotrophic denitrification filler for denitrification and a preparation method thereof. The autotrophic denitrification filler for denitrification prepared by the present invention has good purification performance and effectively improves the use performance of the autotrophic denitrification filler for denitrification.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] In a first aspect, the present invention provides an autotrophic denitrification filler for denitrification, comprising the following raw materials in parts by weight: 80 to 100 parts of sulfur powder, 8 to 12 parts of zinc carbonate powder, 8 to 12 parts of clay, 4 to 6 parts of ferrosoferric oxide, 4 to 6 parts of polyhydroxyalkanoate, 4 to 6 parts of sugarcane cellulose, 1 to 3 parts of cotton, 1 to 3 parts of a binder, and 1 to 3 parts of a cross-linking agent;

[0007] The sulfur powder is divided into component A, component B and component C, wherein the mass ratio of component A, component B and component C is 1:1.1:1.2, the particle size of the sulfur powder of component A is 110-130 μm, the particle size of the sulfur powder of component B is 70-90 μm, and the particle size of the sulfur powder of component C is 50-70 μm.

[0008] Furthermore, the sulfur powder is pretreated, and the pretreatment method of the sulfur powder is as follows: sulfur powder of component A, sulfur powder of component B and sulfur powder of component C are added into a mixer, and the mixer is set at 200-300 r / min for mixing for 8-12 minutes to obtain a mixture after treatment.

[0009] Furthermore, the mixture is added to a water bath, sodium sulfide solution is added to the water bath, stirred evenly, the water bath is heated to 40-50°C, and the reaction is kept warm for 2-4 hours. After the reaction is completed, the mixture is cooled to room temperature, and the mixture in the water bath is added to an ultrasonic disperser, set at 70-90kHz to process for 16-20 minutes, rinsed with clean water after the treatment, and then sent to an oven, set at 50-60°C for drying for 20-30 minutes to complete the pretreatment of the sulfur powder.

[0010] Furthermore, the mass of the sodium sulfide solution is 20-30% of the mass of the mixture, and the mass concentration of the sodium sulfide solution is 4-6%.

[0011] Furthermore, the clay is kaolin, and the water content of kaolin is ≤2%.

[0012] Furthermore, the binder is selected from at least one of corn starch and carboxymethyl cellulose.

[0013] Furthermore, the cross-linking agent is selected from at least one of acrylic acid, dicyclopentadiene and polystyrene.

[0014] Furthermore, the zinc carbonate powder and ferrosoferric oxide are both selected to have a particle size of ≤80 μm.

[0015] Furthermore, clay, sugarcane cellulose and cotton are pretreated before preparation to obtain an additive, and the additive is obtained by the following method: clay is added to a paddle mixer, clean water is added, and the stirring is set at 80-100 r / min for 6-10 minutes, sugarcane cellulose and cotton are added, and the stirring is set at 160-180 r / min for 10-14 minutes to obtain wet mud, the mud is pressed into a cake, and sent to an oven, set at 60-70°C for drying for 40-50 minutes to obtain dry mud, and the dry mud is crushed and ground to obtain the additive, wherein the mass of clean water is 20-30% of the mass of clay, the temperature when the clean water is added is 50-60°C, and the grinding particle size of the dry mud is 80-100 μm.

[0016] In a second aspect, the present invention also provides a method for preparing an autotrophic denitrification filler for denitrification, comprising the following steps:

[0017] S1: zinc carbonate powder, ferrosoferric oxide, polyhydroxyalkanoate, binder, crosslinking agent and pretreated sulfur powder are added to a mixer, sodium alginate aqueous solution is added to the mixer, and stirring is performed at 120-160 r / min for 4-6 min. After stirring, additives are added, and the mixer is set at 300-340 r / min for stirring for 12-16 min to obtain a paste, wherein the mass concentration of the sodium alginate aqueous solution is 1-3%, and the mass of the sodium alginate aqueous solution is 1.6-2.4 times the mass of the sulfur powder;

[0018] S2: The paste material is sent to the granulator, and the temperature of the feeding end of the granulator is set to 140-160°C, the temperature of the discharging end is set to 220-240°C, the screw speed is set to 40-50r / min, and the particle size is 6-10mm. After granulation is completed, it is waited to cool to room temperature and sent to a vacuum dryer for drying to obtain an autotrophic denitrification filler for denitrification. The vacuum dryer is set to a temperature of 120-140°C, a time of 8-10h, and a vacuum degree of 80-100Pa.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] 1. In the present invention, in the preparation process of the autotrophic denitrification filler for denitrification, sulfur powders of different particle sizes can be mixed together by heating and soaking the mixture in a water bath, ultrasonic dispersion and drying. After the sulfur powder contacts with the sodium sulfide solution, the sulfide ions in the sodium sulfide react with the sulfur molecules to generate polysulfide ions. As the reaction proceeds, the sulfur powder can be dissolved. Then, in the high-frequency ultrasonic treatment, the contact between the sulfur powder and the sodium sulfide is uneven, and then uneven concave dissolution positions can be generated on the surface of the sulfur powder, so that the specific surface area of ​​the sulfur powder is effectively increased. After the filler is made of sulfur powder as the main raw material, the filler has a large contact reaction area with the sewage, which provides a good attachment and growth environment for denitrifying bacteria, thereby improving the purification effect of the autotrophic denitrification filler for denitrification.

[0021] 2. In the present invention, sulfur powder is divided into a plurality of components with different particle sizes, and sulfur powders with a plurality of different particle sizes are mixed to form a filler. The small-particle sulfur powder can be filled in the gaps between the large-particle sulfur powder, so that the concave-convex pore structure on the surface of the filler is more abundant. When water flows through the position of the filler, the water flow can be disturbed, thereby increasing the contact area between the filler and the sewage and promoting the attachment and growth of denitrifying bacteria.

[0022] 3. In the present invention, additives are added in the preparation of the autotrophic denitrification filler for denitrification, the better adhesion of kaolin is used to improve the overall strength of the filler, and the fiber structure of sugarcane cellulose and cotton can be used to further optimize the pore structure of the filler. At the same time, sugarcane cellulose and cotton will slowly decompose under the action of microorganisms to produce an organic carbon source, provide energy for denitrifying bacteria, and improve the purification effect of the filler.

[0023] 4. The addition of ferroferric oxide can provide iron to microorganisms, which is helpful for the growth of denitrifying microorganisms. Polyhydroxyalkanoates can be used in conjunction with additives to provide energy for denitrifying bacteria, further improving the purification effect of the filler. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1The present invention provides a self-trophic denitrification filler for denitrification and its preparation method, and a comparison of the electron microscope characterizations before and after sulfur powder pretreatment. DETAILED DESCRIPTION

[0025] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0026] The present embodiment provides an autotrophic denitrification filler for denitrification, comprising the following raw materials in parts by weight: 80-100 parts of sulfur powder, 8-12 parts of zinc carbonate powder, 8-12 parts of clay, 4-6 parts of ferrosoferric oxide, 4-6 parts of polyhydroxyalkanoate, 4-6 parts of sugarcane cellulose, 1-3 parts of cotton, 1-3 parts of a binder, and 1-3 parts of a cross-linking agent;

[0027] The sulfur powder is divided into component A, component B and component C, wherein the mass ratio of component A, component B and component C is 1:1.1:1.2, the particle size of the sulfur powder of component A is 110-130μm, the particle size of the sulfur powder of component B is 70-90μm, and the particle size of the sulfur powder of component C is 50-70μm.

[0028] In some embodiments, the sulfur powder is pretreated, and the pretreatment method of the sulfur powder is: component A sulfur powder, component B sulfur powder and component C sulfur powder are added into a mixer, and the mixer is set at 200-300 r / min for mixing for 8-12 minutes to obtain a mixture after treatment.

[0029] In some embodiments, the mixture is added to a water bath, sodium sulfide solution is added to the water bath, stirred evenly, the water bath temperature is raised to 40-50°C, and the reaction is kept warm for 2-4 hours. After the reaction is completed, wait for it to cool to room temperature, add the mixture in the water bath to an ultrasonic disperser, set 70-90kHz to process for 16-20 minutes, rinse with clean water after the treatment, send it to an oven after rinsing, set 50-60°C to dry for 20-30 minutes, and complete the pretreatment of sulfur powder.

[0030] In some embodiments, the mass of the sodium sulfide solution is 20-30% of the mass of the mixture, and the mass concentration of the sodium sulfide solution is 4-6%.

[0031] In some embodiments, the clay is kaolin, and the water content of kaolin is ≤2%.

[0032] In some embodiments, the binder is at least one of corn starch and carboxymethyl cellulose.

[0033] In some embodiments, the cross-linking agent is selected from at least one of acrylic acid, dicyclopentadiene, and polystyrene.

[0034] In some embodiments, the zinc carbonate powder and ferrosoferric oxide are both selected to have a particle size of ≤80 μm.

[0035] In some embodiments, clay, sugarcane cellulose and cotton are pretreated before preparation to obtain an additive, and the additive is obtained by the following method: clay is added to a paddle mixer, clean water is added, and the stirring is set at 80-100 r / min for 6-10 minutes, sugarcane cellulose and cotton are added, and the stirring is set at 160-180 r / min for 10-14 minutes to obtain wet mud, the mud is pressed into a cake, and sent to an oven, set at 60-70°C for drying for 40-50 minutes to obtain dry mud, and the dry mud is crushed and ground to obtain the additive, wherein the mass of clean water is 20-30% of the mass of clay, the temperature when the clean water is added is 50-60°C, and the grinding particle size of the dry mud is 80-100 μm.

[0036] In some embodiments, a method for preparing an autotrophic denitrification filler for denitrification comprises the following steps:

[0037] S1: zinc carbonate powder, ferrosoferric oxide, polyhydroxyalkanoate, binder, crosslinking agent and pretreated sulfur powder are added to a mixer, sodium alginate aqueous solution is added to the mixer, and stirring is performed at 120-160 r / min for 4-6 min. After stirring, additives are added, and the mixer is set at 300-340 r / min for stirring for 12-16 min to obtain a paste, wherein the mass concentration of the sodium alginate aqueous solution is 1-3%, and the mass of the sodium alginate aqueous solution is 1.6-2.4 times the mass of the sulfur powder;

[0038] S2: The paste material is sent to the granulator, and the temperature of the feeding end of the granulator is set to 140-160°C, the temperature of the discharging end is set to 220-240°C, the screw speed is set to 40-50r / min, and the particle size is 6-10mm. After granulation is completed, it is waited to cool to room temperature and sent to a vacuum dryer for drying to obtain an autotrophic denitrification filler for denitrification. The vacuum dryer is set to a temperature of 120-140°C, a time of 8-10h, and a vacuum degree of 80-100Pa.

[0039] In the present embodiment, in the preparation process of the autotrophic denitrification filler for denitrification, sulfur powders of different particle sizes can be mixed together by heating and soaking the mixture in a water bath, ultrasonically dispersing and drying the mixture. After the sulfur powder contacts with the sodium sulfide solution, the sulfide ions in the sodium sulfide react with the sulfur molecules to generate polysulfide ions. As the reaction proceeds, the sulfur powder can be dissolved. Subsequently, in the high-frequency ultrasonic treatment, the contact between the sulfur powder and the sodium sulfide is uneven, and uneven concave dissolution positions can be generated on the surface of the sulfur powder, so that the specific surface area of ​​the sulfur powder is effectively increased. After the filler is made using sulfur powder as the main raw material, the filler has a large contact reaction area with the sewage, which provides a good attachment and growth environment for denitrifying bacteria, thereby improving the autotrophic denitrification filler for denitrification. The purification effect of the material is improved. The sulfur powder is divided into multiple components with different particle sizes. Sulfur powders of multiple different particle sizes are mixed to form fillers. Small-particle sulfur powder can be filled in the gaps of large-particle sulfur powder, making the concave-convex pore structure on the surface of the filler richer. When water flows through the filler position, the water flow can be disturbed, the contact area between the filler and the sewage is increased, and the attachment and growth of denitrifying bacteria are promoted. By adding additives in the preparation of autotrophic denitrification fillers for denitrification, the better adhesion of kaolin is used to improve the overall strength of the filler. The fiber structure of sugarcane cellulose and cotton can further optimize the pore structure of the filler. At the same time, sugarcane cellulose and cotton will slowly decompose under the action of microorganisms to produce organic carbon sources, which provide energy for denitrifying bacteria and improve the purification effect of the filler.

[0040] Based on the above embodiments, the following experiments were performed:

[0041] It should be noted that the raw materials used in the following experiments are all commercially available raw materials.

[0042] Experiment 1:

[0043] Raw material preparation: 80 parts of sulfur powder, 8 parts of zinc carbonate powder, 8 parts of clay, 4 parts of ferroferric oxide, 4 parts of polyhydroxyalkanoate, 4 parts of sugarcane cellulose, 1 part of cotton, 1 part of binder and 1 part of cross-linking agent. The sulfur powder is divided into component A, component B and component C, wherein the mass ratio of component A, component B and component C is 1:1.1:1.2, the particle size of the sulfur powder of component A is 110 μm, the particle size of the sulfur powder of component B is 70 μm, and the particle size of the sulfur powder of component C is 50 μm. Kaolin is selected as the clay, and the water content of kaolin is ≤2%. Corn starch is selected as the binder, acrylic acid is selected as the cross-linking agent, and the particle size of zinc carbonate powder and ferroferric oxide are both selected to be ≤80 μm.

[0044] The pretreatment method of sulfur powder is as follows: sulfur powder of component A, sulfur powder of component B and sulfur powder of component C are added to a mixer, the mixer is set to 200r / min for mixing for 8 minutes, a mixture is obtained after the treatment, the mixture is added to a water bath, sodium sulfide solution is added to the water bath, stirred evenly, the water bath is heated to 40°C, and the reaction is kept warm for 2 hours. After the reaction is completed, it is cooled to room temperature, the mixture in the water bath is added to an ultrasonic disperser, set to 70kHz for 16 minutes, rinsed with clean water after the treatment, and sent to an oven after rinsing, set to 50°C for drying for 20 minutes, and the pretreatment of sulfur powder is completed. The mass of the sodium sulfide solution is 20% of the mass of the mixture, and the mass concentration of the sodium sulfide solution is 4%;

[0045] Before preparation, clay, sugarcane cellulose and cotton were pretreated to obtain an additive, and the additive was obtained by the following method: clay was added to a paddle mixer, clean water was added, and the stirring process was set at 80r / min for 6 minutes, sugarcane cellulose and cotton were added, and the stirring process was set at 160r / min for 10 minutes to obtain wet mud, the mud was pressed into a cake, sent into an oven, and dried at 60°C for 40 minutes to obtain dry mud, and the dry mud was crushed and ground to obtain the additive, wherein the mass of clean water was 20% of the mass of clay, the temperature when the clean water was added was 50°C, and the grinding particle size of the dry mud was 80μm;

[0046] Preparation of autotrophic denitrification filler for nitrogen removal:

[0047] S1: zinc carbonate powder, ferrosoferric oxide, polyhydroxyalkanoate, binder, crosslinking agent and pretreated sulfur powder are added to a mixer, sodium alginate aqueous solution is added to the mixer, and stirring is performed at 120 r / min for 4 min. After stirring, additives are added, and the mixer is set at 300 r / min for stirring for 12 min to obtain a paste, wherein the mass concentration of the sodium alginate aqueous solution is 1%, and the mass of the sodium alginate aqueous solution is 1.6 times the mass of the sulfur powder;

[0048] S2: The paste material is sent to the granulator, the temperature of the feed end of the granulator is set to 140°C, the temperature of the discharge end is set to 220°C, the screw speed is set to 40r / min, and the particle size is 6mm. After the granulation is completed, it is cooled to room temperature and sent to the vacuum dryer for drying to obtain the autotrophic denitrification filler for denitrification. The vacuum dryer is set to a temperature of 120°C, a time of 8h, and a vacuum degree of 80Pa;

[0049] In this experiment, the electron microscope images of sulfur powder before and after pretreatment are shown in Figure 1 ,in, Figure 1Figure a shows the sulfur powder before pretreatment, and Figure b shows the sulfur powder after pretreatment. It can be seen from the figures that the sulfur powder is a mixture of particles of different sizes before pretreatment. After pretreatment, uneven concave dissolution positions are generated on the surface of the sulfur powder, which effectively increases the specific surface area of ​​the sulfur powder.

[0050] Experiment 2:

[0051] Raw material preparation: 90 parts of sulfur powder, 10 parts of zinc carbonate powder, 10 parts of clay, 5 parts of ferroferric oxide, 5 parts of polyhydroxyalkanoate, 5 parts of sugarcane cellulose, 2 parts of cotton, 2 parts of binder and 2 parts of cross-linking agent. The sulfur powder is divided into component A, component B and component C, wherein the mass ratio of component A, component B and component C is 1:1.1:1.2, the particle size of the sulfur powder of component A is 120 μm, the particle size of the sulfur powder of component B is 80 μm, and the particle size of the sulfur powder of component C is 60 μm. Kaolin is selected as the clay, and the water content of kaolin is ≤2%. Carboxymethyl cellulose is selected as the binder, dicyclopentadiene is selected as the cross-linking agent, and the particle size of zinc carbonate powder and ferroferric oxide are both selected to be ≤80 μm.

[0052] The pretreatment method of sulfur powder is as follows: sulfur powder of component A, sulfur powder of component B and sulfur powder of component C are added to a mixer, the mixer is set to 250r / min for mixing for 10 minutes, a mixture is obtained after the treatment, the mixture is added to a water bath, sodium sulfide solution is added to the water bath, stirred evenly, the water bath is heated to 45°C, and the reaction is kept warm for 3 hours. After the reaction is completed, it is waited to cool to room temperature, the mixture in the water bath is added to an ultrasonic disperser, set to 80kHz for 18 minutes, rinsed with clean water after the treatment, and sent to an oven after rinsing, set to 55°C for drying for 25 minutes, and the pretreatment of sulfur powder is completed. The mass of the sodium sulfide solution is 25% of the mass of the mixture, and the mass concentration of the sodium sulfide solution is 5%;

[0053] Before preparation, clay, sugarcane cellulose and cotton were pretreated to obtain an additive, and the additive was obtained by the following method: clay was added to a paddle mixer, clean water was added, and stirring was performed at 90 r / min for 8 minutes, sugarcane cellulose and cotton were added, and stirring was performed at 170 r / min for 12 minutes to obtain wet mud, the mud was pressed into a cake, sent into an oven, and dried at 65° C. for 55 minutes to obtain dry mud, and the dry mud was crushed and ground to obtain the additive, wherein the mass of clean water was 25% of the mass of clay, the temperature when the clean water was added was 55° C., and the grinding particle size of the dry mud was 90 μm;

[0054] Preparation of autotrophic denitrification filler for nitrogen removal:

[0055] S1: zinc carbonate powder, ferrosoferric oxide, polyhydroxyalkanoate, binder, crosslinking agent and pretreated sulfur powder are added to a mixer, sodium alginate aqueous solution is added to the mixer, and stirring is performed at 140 r / min for 5 min. After stirring, additives are added, and the mixer is set at 320 r / min for stirring for 14 min to obtain a paste, wherein the mass concentration of the sodium alginate aqueous solution is 2%, and the mass of the sodium alginate aqueous solution is twice the mass of the sulfur powder;

[0056] S2: The paste material is sent to the granulator. The temperature of the feed end of the granulator is set to 150°C, the temperature of the discharge end is set to 230°C, the screw speed is 45r / min, and the particle size is 8mm. After granulation is completed, it is cooled to room temperature and sent to a vacuum dryer for drying to obtain an autotrophic denitrification filler for denitrification. The vacuum dryer is set to a temperature of 130°C, a time of 9h, and a vacuum degree of 90Pa.

[0057] Experiment 3:

[0058] Raw material preparation: 100 parts of sulfur powder, 12 parts of zinc carbonate powder, 12 parts of clay, 6 parts of ferroferric oxide, 6 parts of polyhydroxyalkanoate, 6 parts of sugarcane cellulose, 3 parts of cotton, 3 parts of binder and 3 parts of cross-linking agent. The sulfur powder is divided into component A, component B and component C, wherein the mass ratio of component A, component B and component C is 1:1.1:1.2, the particle size of the sulfur powder of component A is 130 μm, the particle size of the sulfur powder of component B is 90 μm, and the particle size of the sulfur powder of component C is 70 μm. Kaolin is selected as the clay, and the water content of kaolin is ≤2%. Corn starch is selected as the binder, polystyrene is selected as the cross-linking agent, and the particle size of zinc carbonate powder and ferroferric oxide are both selected to be ≤80 μm.

[0059] The pretreatment method of sulfur powder is as follows: sulfur powder of component A, sulfur powder of component B and sulfur powder of component C are added to a mixer, the mixer is set to 300r / min for mixing for 12 minutes, a mixture is obtained after treatment, the mixture is added to a water bath, sodium sulfide solution is added to the water bath, stirred evenly, the water bath is heated to 50°C, and the reaction is kept warm for 4 hours. After the reaction is completed, it is waited to cool to room temperature, the mixture in the water bath is added to an ultrasonic disperser, set to 90kHz for 20 minutes, rinsed with clean water after the treatment, and sent to an oven after rinsing, set to 60°C for drying for 30 minutes, and the pretreatment of sulfur powder is completed. The mass of sodium sulfide solution is 30% of the mass of the mixture, and the mass concentration of sodium sulfide solution is 6%;

[0060] Before preparation, clay, sugarcane cellulose and cotton were pretreated to obtain an additive, and the additive was obtained by the following method: clay was added to a paddle mixer, clean water was added, and the mixture was stirred at 100 r / min for 10 min, sugarcane cellulose and cotton were added, and the mixture was stirred at 180 r / min for 14 min to obtain wet mud, the mud was pressed into a cake, and sent to an oven, and dried at 70°C for 50 min to obtain dry mud, and the dry mud was crushed and ground to obtain the additive, wherein the mass of clean water was 30% of the mass of clay, the temperature when the clean water was added was 60°C, and the grinding particle size of the dry mud was 100 μm;

[0061] Preparation of autotrophic denitrification filler for nitrogen removal:

[0062] S1: zinc carbonate powder, ferrosoferric oxide, polyhydroxyalkanoate, binder, crosslinking agent and pretreated sulfur powder are added to a mixer, sodium alginate aqueous solution is added to the mixer, and stirring is performed at 160 r / min for 6 min. After stirring, additives are added, and the mixer is set at 340 r / min for stirring for 16 min to obtain a paste, wherein the mass concentration of the sodium alginate aqueous solution is 3%, and the mass of the sodium alginate aqueous solution is 2.4 times the mass of the sulfur powder;

[0063] S2: The paste material is sent to the granulator, and the temperature of the feed end of the granulator is set to 160°C, the temperature of the discharge end is set to 240°C, the screw speed is 50r / min, and the particle size is 10mm. After granulation is completed, wait for cooling to room temperature and send it to a vacuum dryer for drying to obtain an autotrophic denitrification filler for denitrification. The vacuum dryer is set to a temperature of 140°C, a time of 10h, and a vacuum degree of 100Pa.

[0064] Comparative Example 1: The difference between this comparative example and Experiment 1 is that this comparative example does not contain sugarcane cellulose and cotton.

[0065] Comparative Example 2: The difference between this comparative example and Experiment 1 is that this comparative example does not contain any additives.

[0066] Comparative Example 3: The difference between this comparative example and Experiment 1 is that the sulfur powder is not pretreated in this comparative example.

[0067] Comparative Example 4: The difference between this comparative example and Experiment 1 is that no ultrasonic dispersion treatment is performed in this comparative example.

[0068] Performance test: The autotrophic denitrification fillers for denitrification prepared in Experiment 1, Experiment 2, Experiment 3, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4 were tested for performance, and the test data obtained are recorded in the following table:

[0069]

[0070] In the performance test, the autotrophic denitrification fillers for denitrification prepared in Experiment 1, Experiment 2, Experiment 3, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4 were respectively filled into the simulated denitrification reactor. The reactor volume was 15L, the filling amount was 30%, and 1.5L of Desulfurization Bacillus solution with a mass concentration of 40% was inoculated. Domestic sewage was input, and the residence time was 2h. The nitrate-nitrogen values ​​before and after the sewage input were measured, and the removal rate of the autotrophic denitrification filler for denitrification was calculated.

[0071] By comparing and analyzing the relevant data in the table, it can be seen that the autotrophic denitrification filler for denitrification prepared by the present invention has good purification performance. This shows that the autotrophic denitrification filler for denitrification and the preparation method thereof provided by the present invention have a broader market prospect and are more suitable for promotion.

[0072] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0073] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. An autotrophic denitrification filler for denitrification, characterized in that: The method comprises the following raw materials in parts by weight: 80 to 100 parts of sulfur powder, 8 to 12 parts of zinc carbonate powder, 8 to 12 parts of clay, 4 to 6 parts of ferroferric oxide, 4 to 6 parts of polyhydroxyalkanoate, 4 to 6 parts of sugarcane cellulose, 1 to 3 parts of cotton, 1 to 3 parts of a binder and 1 to 3 parts of a cross-linking agent; The sulfur powder is divided into component A, component B and component C, wherein the mass ratio of component A, component B and component C is 1:1.1:1.2, the particle size of the sulfur powder of component A is 110-130 μm, the particle size of the sulfur powder of component B is 70-90 μm, and the particle size of the sulfur powder of component C is 50-70 μm; The sulfur powder is pretreated, and the pretreatment method of the sulfur powder is as follows: the sulfur powder of component A, the sulfur powder of component B and the sulfur powder of component C are added into a mixer, and the mixer is set at 200-300 r / min for mixing for 8-12 minutes to obtain a mixture after the treatment; The mixture is added into a water bath, sodium sulfide solution is added into the water bath, stirred evenly, the water bath is heated to 40-50° C., kept warm for reaction for 2-4 hours, and after the reaction is completed, wait for cooling to room temperature, add the mixture in the water bath into an ultrasonic disperser, set 70-90kHz to process for 16-20 minutes, rinse with clean water after the treatment, send into an oven after rinsing, set 50-60° C. to dry for 20-30 minutes, and complete the pretreatment of sulfur powder.

2. The autotrophic denitrification filler for denitrification according to claim 1, characterized in that: The mass of the sodium sulfide solution is 20-30% of the mass of the mixed material, and the mass concentration of the sodium sulfide solution is 4-6%.

3. The autotrophic denitrification filler for denitrification according to claim 1, characterized in that: The clay is kaolin, and the water content of kaolin is ≤2%.

4. The autotrophic denitrification filler for denitrification according to claim 1, characterized in that: The binder is selected from at least one of corn starch and carboxymethyl cellulose.

5. The autotrophic denitrification filler for denitrification according to claim 1, characterized in that: The cross-linking agent is selected from at least one of acrylic acid, dicyclopentadiene and polystyrene.

6. The autotrophic denitrification filler for denitrification according to claim 1, characterized in that: The zinc carbonate powder and ferrosoferric oxide are both selected to have a particle size of ≤80 μm.

7. The autotrophic denitrification filler for denitrification according to claim 1, characterized in that: Before preparation, clay, sugarcane cellulose and cotton are pretreated to obtain an additive, and the additive is obtained by the following method: clay is added into a paddle mixer, clean water is added, and the stirring process is set at 80-100r / min for 6-10min, sugarcane cellulose and cotton are added, and the stirring process is set at 160-180r / min for 10-14min to obtain wet mud, the mud is pressed into a cake, sent into an oven, and dried at 60-70°C for 40-50min to obtain dry mud, and the dry mud is crushed and ground to obtain the additive, wherein the mass of the clean water is 20-30% of the mass of the clay, the temperature when the clean water is added is 50-60°C, and the grinding particle size of the dry mud is 80-100μm.

8. A method for preparing the autotrophic denitrification filler for denitrification according to claim 7, characterized in that: The following steps are involved: S1: zinc carbonate powder, ferrosoferric oxide, polyhydroxyalkanoate, binder, crosslinking agent and pretreated sulfur powder are added to a mixer, sodium alginate aqueous solution is added to the mixer, and stirring is performed at 120-160 r / min for 4-6 min. After stirring, additives are added, and the mixer is set at 300-340 r / min for stirring for 12-16 min to obtain a paste, wherein the mass concentration of the sodium alginate aqueous solution is 1-3%, and the mass of the sodium alginate aqueous solution is 1.6-2.4 times the mass of the sulfur powder; S2: The paste material is sent to the granulator, and the temperature of the feeding end of the granulator is set to 140-160°C, the temperature of the discharging end is set to 220-240°C, the screw speed is set to 40-50r / min, and the particle size is 6-10mm. After granulation is completed, it is waited to cool to room temperature and sent to a vacuum dryer for drying to obtain an autotrophic denitrification filler for denitrification. The vacuum dryer is set to a temperature of 120-140°C, a time of 8-10h, and a vacuum degree of 80-100Pa.

Citation Information

Patent Citations

  • Anticorrosive wear-resistant water-based filler and preparation method and application thereof in coating

    CN111892853A

  • Functional material for removing nitrate nitrogen in water and preparation and application methods thereof

    CN112390380A